2009
DOI: 10.1111/j.1600-0579.2008.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Who will pass the dental OSCE? Comparison of the Angoff and the borderline regression standard setting methods

Abstract: Therefore we conclude that the BR method in a PC model provides defensible pass/fail standards and seems to be the optimal choice for OSCEs in health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…Similarly, in a study by Byrne and Smyth, preregistration nursing students felt so stressed that it had a negative impact on their performance in an OSCE assessment [31]. However, Byrne and Smyth concluded that students already exposed to an OSCE described feeling less anxious and better prepared for their subsequent clinical placements.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, in a study by Byrne and Smyth, preregistration nursing students felt so stressed that it had a negative impact on their performance in an OSCE assessment [31]. However, Byrne and Smyth concluded that students already exposed to an OSCE described feeling less anxious and better prepared for their subsequent clinical placements.…”
Section: Resultsmentioning
confidence: 98%
“…Borderline regression: This standard setting method has gained favour in recent years 9 in both medical and dental education due to its advantages in OSCE assessments. In this method, examiners are asked to complete the mark sheet for a candidate sitting an individual station (which may have previously been standard set using an alternative technique, such as Angoff).…”
Section: Standard Setting Techniquesmentioning
confidence: 99%
“…The use of the objective structured clinical examination has found its place in the assessment of clinical competency in medicine (Harden, Stevenson et al 1975;Kaufman, Mann et al 2000;Boulet, De Champlain et al 2003;Boursicot 2006;Harden and Gleeson 2009) and other health profession (Schoonheim-Klein, Muijtjens et al 2009); however, this is the first report of the successful use of the OSCE and performance based standard setting in the assessment of clinical competency for undergraduate dispensing opticians. Further research is required to confirm our initial impressions from this pilot study, that the OSCE and BR method of performance based standard setting is a practical and acceptable option for the certification of professional competency for dispensing opticians.…”
Section: Discussionmentioning
confidence: 97%